Education on Medication Management at the "Tresna Werdha Jombang" Nursing Home – Kediri - Hanie Kusuma Wardani; Juvita Herdianti; Arif Wijayanto; Janik Kurniawati (Journal of Community Engagement in Health, 2024)
The elderly population residing in nursing home requires special attention, because elderly people often have diabetes, hypertension and other chronic diseases which require them to store medicines to be taken regularly every day. Therefore, elderly people are required to understand drug management, namely how to obtain, use, store, and dispose of drugs. Inadequate understanding of medication management for the elderly in nursing home can cause damage to stored medication, resulting in a decrease in the effectiveness of the medication. The aim of this activity is to increase the understanding of elderly in terms of medication management. The community service method is in the form of a seminar with the opening stages, material presentation, and closing. The results of the activity lasted for 3 hours with 30 participants, and presentations from 4 speakers on the topic of how to obtain, use, store and dispose of medication properly and correctly. This activity went very well and the evaluation was calculated at the end. Through this educational activity, participants gain an understanding of how to obtain, use, store and dispose of medication properly and correctly so that medication can be used optimally and avoid swallowing expired medication by elderly people in nursing homes.